The Relationship Of Nurse Caring Behavior With Anxiety Level In Covid 19 Patients In The Tulip And Orchid Isolation Room UPT RSUD Deli Serdang - Nurlela Petra saragih; Intan Mutia Rahmi; Rini Elvira Hutabarat; Sontina Saragih (Science Midwifery, 2022)
Coronavirus 19 (COVID-19) has been declared a world pandemic by WHO (WHO, 2020). Anxiety in patients with a confirmed COVID-19 suspicion requires close medical observation and isolation during treatment. Nurses are one of the health professionals who still have to work and continue to serve in the current Covid-19 pandemic situation. Based on this, the researchers were interested in obtaining information about "The relationship between nurse caring behavior and the anxiety level of Covid 19 patients in the Tulip and Anggrek isolation room at the UPT RSUD Deli Serdang."This research uses analytical method, cross sectional. The sample in this study amounted to 59 patients with a diagnosis of Covid 19, which was obtained based on a population average of 146 people every month. The results of the study concluded that there was a significant relationship between nurse caring behavior and anxiety levels in Covid 19 patients in the Tulip and Anggrek isolation room at the UPT Deli Serdang Hospital. Nurses should improve caring behavior, especially in Covid 19 patients who need psychological support such as strengthening health education, and actively directing patients to be open in counseling.